Early versus late spinal decompression surgery in treatment of traumatic spinal cord injuries; a systematic review and meta-analysis - Yousefifard, Mahmoud (Emerg (Tehran), 2017)
INTRODUCTION: Despite the vast number of surveys, no consensus has been reached on the optimum timing of spinal decompression surgery. This systematic review and meta-analysis aimed to compare the effects of early and latespinal decompression surgery on neurologic improvement and post-surgical complications in patients with traumatic spinal cord injuries. METHODS: Two independent reviewers carried out an extended search in electronic databases. Data of neurological outcome and post-surgery complication were extracted. Finally, pooled relative risk (RR) with a 95% confidence interval (CI) was reported for comparing of efficacy of early and late surgical decompression. RESULTS: Eventually 22 studies were included. The pooled RRwas 0.77 (95% CI: 0.68-0.89)for at least one grade neurological improvement, and 0.84 (95% CI: 0.77-0.92)for at least two grade improvement. Pooled RR for surgical decompression performed within 12 hours after the injury was 0.26 (95% CI: 0.13-0.52; p<0.001), while it was 0.75 (95% CI: 0.63-0.90; p=0.002) when the procedure was performed within 24 hours, and 0.93 (95% CI: 0.76-1.14; p=0.48) when it was carried out in the first 72 hours after the injury. Surgical decompression performed within 24 hours after injury was found to be associated with significantly lower rates of post-surgical complications (RR=0.77; 95% CI: 0.68-0.86; p<0.001). CONCLUSION: The findings of this study indicate that early spinal decompression surgery can improve neurologic recovery and is associated with less post-surgical complications. The optimum efficacy is observed when the procedure is performed within 12 hours of the injury.